Barriers & enablers of E-Government Procurement (E-GP): an analysis of Public Works Department (PWD) - Haider, Jubair Bin (BRAC University, 2017)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.